2022
DOI: 10.36312/jime.v8i2.3127
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Case Method Dalam Meningkatkan Hasil Belajar Mahasiswa

Abstract: The counselors/professional guidance and counseling teachers is a teachers/counselors that can counseling and guidance services in schools on a planned, systematic and responsible manner. Professional counselors/teachers are educated in academic institutions that have effective and innovative learning methods. The case method can improve students' ability to analyze and solves problem. Thus study aims to determine how the description of student learning outcomes and whether the application of the case method c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…Strategi pembelajaran Case method dan team-based project merupakan model pembelajaran inovatif yang melibatkan kerja proyek di mana mahasiswa membangun proses pembelajarannya sendiri dan menerjemahkannya ke dalam sebuah produk nyata (Siagian, Dalam hal ini mahasiswa mencoba menemukan sekaligus berupaya mensolusikan masalah yang ditemukan dengan luaran produk desain. Dosen berperan sebagai facilitator, initiator, director, participant dan motivator dalam proses pembelajaran model case method dan team based project (Syam, 2022).…”
Section: Pendahuluanunclassified
“…Strategi pembelajaran Case method dan team-based project merupakan model pembelajaran inovatif yang melibatkan kerja proyek di mana mahasiswa membangun proses pembelajarannya sendiri dan menerjemahkannya ke dalam sebuah produk nyata (Siagian, Dalam hal ini mahasiswa mencoba menemukan sekaligus berupaya mensolusikan masalah yang ditemukan dengan luaran produk desain. Dosen berperan sebagai facilitator, initiator, director, participant dan motivator dalam proses pembelajaran model case method dan team based project (Syam, 2022).…”
Section: Pendahuluanunclassified
“…The aim is to foster the development of students' cognitive, affective, and psychomotor competencies (Akhyaruddin, 2022). Supporting this, research by Syam (2022) demonstrates that the case method enhances students' problem-solving abilities by prompting them to analyze and address the issues at hand effectively. Furthermore, this method is a subset of problem-based learning (PBL) or case-based learning (CBL), both of which are integral to promoting student-centered learning environments (Telaumbanua et al, 2022).…”
Section: Introductionmentioning
confidence: 96%
“…According to previous research that has been carried out, the application of the Higher Order Thinking Skill (HOTS) method in the learning process can improve the ability to analyze, evaluate, and create new, useful things [6]. Likewise, other research also found that the case method applied to students' learning process was able to improve students' abilities in analyzing and solving the problems they faced [7]. Therefore, the combination of Higher Order Thinking Skill (HOTS) and Case Method content in one teaching material will be able to improve students' high-level thinking abilities.…”
Section: Introductionmentioning
confidence: 99%